KETERBUKAAN INFORMASI PUBLIK PADA ERA 4.0 DI INDONESIA - Muhammad Adib Adib Alfarisi; Heriyanto Heriyanto (Jurnal Penelitian Administrasi Publik, 2021)
ABSTRACT This study aims to determine the role of public information disclosure in order to support the creation of good governance in the 4.0 era in Indonesia. The research method used in this research is descriptive qualitative method with the aim of systematically, factually, and accurately describing the facts being investigated. Triangulation technique is used to analyze data and is also a technique for checking data validation that utilizes something different outside the data for the purpose of checking comparisons of the same data from other sources. Research finding shows that there is a change in the governance system from a knowledge society to e-government. Through e-government, all information related to public policy will be open to the public. Information disclosure is a form of implementing good governance. Disclosure of information can prevent all forms of Collusion, Corruption or Nepotism that are rife in Indonesia. This prevention is due to the form of control from the community on the performance of the government (central and regional). Furthermore, with the disclosure of information, the public becomes sensitive, intelligent and active in controlling the process of administering a government. Keywords: Information Disclosure, and Prevention of Corruption, Collusion, and Nepotism, and Good Governance